Psychological style as a way to study human diversity: An example based on life styles - Sánchez López, María del Pilar (1997)
This paper considers Psychological Style (PS) as a supraordinal category in the personality organization andas an approach of change. The PS organizes behavior, has an eminet global character, is essential for interpretation, and could be considered as a set of guidelines. Given its encompassing nature, PS is useful in many fields. An empírica! research on Life Styles (LS) is presented, in which is proposed its operativization through time distribution. An original instrument on time distribution is given (AD IT). The data collected indicated that time distribution can be used as an operativisation of LS, since the profiles found have a clear psychological significance and the relation with demographic variables also have a psychological meaning.